Lymphatic tissue of the intestinal tract of germfree and conventional rabbits - Stĕpánková, R; Kovárů, F; Kruml, J (Folia microbiologica, 1980)
The lymphatic tissue of ileum, sacculus rotundus and appendix was poorly developed without germinal centres in germfree rabbits; on the other hand, in conventional rabbits, the lymphatic tissue was abundant with numerous germinal centers. In germfree rabbits, the stroma of villi of the jejunum and ileum possessed low cellularity, in conventional rabbits, the villi were wide with rich cellularity. The basal position of lymphocytes was predominant in the villi of ileum of germfree rabbits, in conventional rabbits a high percentage of lymphocytes was in the apical position.
Keywords: Lymphoid Tissue; lymfoidní tkáň; jejunum; dieta; Jejunum; Intestines; Appendix; Lymphocytes; lymfocyty; Ileum; ileum; gnotobiologické modely; střeva; zvířata; králíci; Germ-Free Life; Rabbits; Diet; apendix; Animals